Expressive Illocutionary Speech Acts in Arabic Comments on X @ar_khamenei: Pragmatic Studyc Study - Abdul Kholiq Permana; Tajudin Nur (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
Social media platform X has become a major space where users express emotional responses to global events. Previous studies on expressive speech acts on X have primarily examined local political figures or general social issues, whereas Arabic-language comments on the official account of a global religious-political figure following the figure's death remain underexplored. This study aims to identify the types and functions of expressive illocutionary speech acts in Arabic-language comments posted on the @ar_khamenei X account following the death of Ali Khamenei. A qualitative descriptive approach employing non-participant observation (Simak Bebas Libat Cakap) was used. The analysis was based on Searle's (1979) theory of expressive speech acts and Leech's (1983) classification of illocutionary functions. The data comprised 78 Arabic-language comments collected from a post published on 1 March 2026. The findings revealed that praying was the most dominant speech act (41 instances; 35 imprecatory prayers and 6 beneficent prayers), followed by insulting (19), thanking God (8), condoling (7), congratulating (2), and blaming (1). The conflictive function predominated (65 instances), while the convivial function occurred in 13 instances; no competitive or collaborative functions were identified. These findings demonstrate that Arabic digital discourse reflects users' sociopolitical, ideological, and religious orientations.